2023
DOI: 10.3389/fnetp.2023.1099282
|View full text |Cite
|
Sign up to set email alerts
|

Measuring pain and nociception: Through the glasses of a computational scientist. Transdisciplinary overview of methods

Abstract: In a healthy state, pain plays an important role in natural biofeedback loops and helps to detect and prevent potentially harmful stimuli and situations. However, pain can become chronic and as such a pathological condition, losing its informative and adaptive function. Efficient pain treatment remains a largely unmet clinical need. One promising route to improve the characterization of pain, and with that the potential for more effective pain therapies, is the integration of different data modalities through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 212 publications
0
3
0
Order By: Relevance
“…Microneurography is an electrophysiological method enabling the extracellular recording of single action potentials (APs) of peripheral nerve bers in awake humans [1,2]. It offers an exclusive approach to examining neuronal discharges leading to itch and pain sensations in both healthy volunteers and patients suffering from chronic pain and itch [3]. Previous microneurography studies showed, for example, the links between spontaneous activity in C-bers and neuropathic pain in humans [4].…”
Section: Introductionmentioning
confidence: 99%
“…Microneurography is an electrophysiological method enabling the extracellular recording of single action potentials (APs) of peripheral nerve bers in awake humans [1,2]. It offers an exclusive approach to examining neuronal discharges leading to itch and pain sensations in both healthy volunteers and patients suffering from chronic pain and itch [3]. Previous microneurography studies showed, for example, the links between spontaneous activity in C-bers and neuropathic pain in humans [4].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we present a solution for managing metadata based on odML and odML-tables for microneurography (see [3,4] for more details), a unique electrophysiological method for observing the activity of single peripheral nerve fibers in awake healthy humans and patients with neuropathy, chronic pain or itch [5,6]. In the field of microneurography, each direct neural recording is very valuable, particularly from patients with diseases caused by rare genetic variants.…”
Section: Introductionmentioning
confidence: 99%
“…However, nociception can best be described as the neurological processing and encoding of intense and noxious stimuli in the human body. Nociceptive signals are mainly expressed as a pain sensation [2]. Pain is a feeling sometimes characterized by inflammation.…”
Section: Introductionmentioning
confidence: 99%